Impact of fiscal variables on economic development of Pakistan - Zaheer Khan Kakar (Romanian Journal of Fiscal Policy (RJFP), 2011)
The objective of this paper is to determine the impact of the fiscal variables on economic growth in Pakistan using time series data for the period 1980-2009. Cointegration and error correction techniques are used for this analysis and Granger causality test is used to determine the direction of causality. This study will provide help in determining the importance of fiscal policy for the development of Pakistan.
Keywords: E0; H87; 330; fiscal policy; economic growth; cointegration; error correction; Granger causality